Complete Resolution of Lymphoid Interstitial Pneumonia in a Patient With Juvenile Myelomonocytic Leukemia Treated With Allogeneic Bone Marrow Transplant: Killing 2 Birds With 1 Stone. Issue 5 (July 2018) - Vatsayan, Anant; Talati, Ravi; Nagle, Kristen; Cabral, Linda; Cammock, Sloane; Dimarino, Amy; Egler, Rachel; Saab, Shahrazad; Dalal, Jignesh
Abstract : Lymphoid interstitial pneumonia (LIP) is a rare disease characterized by benign reactive polyclonal proliferation of bronchus-associated lymphoid tissue after exposure to inhaled or circulating antigen(s), leading to a disease symptomatology similar to idiopathic interstitial pneumonia. Its association with diseases that are caused due to immune dysregulation (autoimmune diseases, congenital/acquired immunodeficiency, and allogeneic bone marrow transplant) and response to immunomodulatory/suppressive medications suggests an immunologic pathophysiology. Although LIP has been reported in association with lymphoproliferative diseases like Castleman disease, it has never been described in patients with leukemia. We report the first case of LIP in a patient with juvenile myelomonocytic leukemia (JMML) who was found to have a novel germline mutation of unknown significance in additional sex combs-like-1 ( ASXL1 ) gene and a pathogenic somatic mutation of protein tyrosine phosphatase, nonreceptor type 11 ( PTPN11 ) gene at diagnosis. The patient underwent a matched unrelated bone marrow transplant for JMML with complete resolution of JMML and LIP with no recurrence to date. We also emphasize the importance of considering LIP in differential diagnosis of pulmonary lesions seen in conjunction with hematologic malignancies and distinguishing it from malignant infiltration of the lung. Abstract : Supplemental Digital Content is available in the text.